Statin gap in patients living with HIV: assessing dose appropriateness. Issue 10 (8th August 2021) - Pincus, Kathleen J.; Blackman, Alison L.; Suen, Samuel Y.; Devabhakthuni, Sandeep; Gale, Stormi; Noel, Zachary R.; Seung, Hyunuk; Pandit, Neha Sheth
Abstract: Objectives: Patients living with HIV (PLWH) are predisposed to atherosclerotic cardiovascular disease (ASCVD), resulting in concomitant antiretroviral and statin use. A statin prescribing gap for PLWH has been reported, but appropriateness of statin selection and dosing (ASD) has not been described. Methods: This is a comparative, retrospective study reviewing ASD in PLWH vs . uninfected patients at two outpatient clinics within an academic medical centre. Adults > 21 years old indicated for statin therapy were included. The primary outcome was percentage of PLWH prescribed an appropriately dosed statin, accounting for clinical‐ and patient‐related variables, compared with uninfected patients. The secondary outcome was to identify patient characteristics associated with inappropriately dosed statins. Results: After propensity score matching, 879 PLWH and 879 uninfected patients were included for analysis. Fewer PLWH (27.8%, n  = 244) were prescribed an ASD compared with uninfected patients (40.5%, n  = 356, P  < 0.001). Similar rates of statin omission were seen in both populations ( P  = 0.11). More PLWH received too low a dose compared with the uninfected population ( P  < 0.0064). There were lower ASD rates in PLWH for subgroups of patients with clinical ASCVD ( P  = 0.00013) and 10‐year ASCVD risk ≥7.5% ( P  = 0.00055), but not in patients with low‐density lipoprotein cholesterol ≥190 mg/dL or diabetes. Conclusions: Although a statin gap exists in both PLWH and uninfected patients, the clinical significance may be greater for PLWH given the increased risk of ASCVD. This study confirms a larger statin gap in PLWH, particularly when underdosing of statin medications is considered. Additional analysis is warranted to investigate reasons for the ASD gap and beneficial clinical interventions.